(untitled) (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2017)
There are few specific, validated vocational training programs for individuals with Autism Spectrum Disorder (ASD). The Practical Assessment Exploration System (PAES) is a functional vocational skills training tool that teaches and measures vocational potential in individuals with developmental disabilities. This project utilized a mixed methods approach to better understand the effectiveness of PAES in enhancing the vocational abilities of twelve adolescents and young adults with ASD. Results indicate a statistically significant improvement in vocational skill and behaviour after completing PAES. Additional qualitative interviews with parents and attendees highlight four primary themes: strengths, benefits derived, limitations, and program suggestions. Implications of these findings are discussed.